Maladaptive Daydreaming: Epidemiological Data on a Newly Identified Syndrome - Soffer-Dudek, Nirit; Theodor-Katz, Nitzan (Frontiers in Psychiatry, 2022)
Background Maladaptive Daydreaming (MD) is a recently identified psychological disorder, characterized by excessively and addictively engaging in vivid, narrative, intensely emotional fantasy activity, at times with the aid of music and/or repetitive movements, causing distress and functional impairment. Over 100,000 self-diagnosed individuals are active online and thousands of them have been researched; yet there are no studies using clinical interviews on large, systematic general (non-MD) samples, to assess the estimated prevalence of this suggested disorder, and establish norms for its main psychometric tool. Methods Four independent Israeli samples (three student samples, and one sample representing the general Jewish-Israeli population; total N = 1,023) self-reported MD. In two samples, those exceeding the cutoff score for suspected MD were invited for a structured clinical interview. Results The skewness of most items of the 16-item Maladaptive Daydreaming Scale (MDS-16) supports the notion of MD as a binary construct rather than a normally distributed trait. In the community sample, 4.2% exceeded the cutoff for suspected MD. Rates were higher when focusing on the young adult age group or student samples (5.5–8.5%), suggesting a likely age effect. Following clinical interviews, only 60% of interviewed respondents met criteria for diagnosis, suggesting a true point-prevalence of 2.5% in the Israeli-Jewish population. Conclusions This is the first systematic clinical evaluation of the prevalence of MD. In an Israeli sample, a point-prevalence of 2.5% was found, like several other internalizing psychiatric syndromes. This result, along with the Non-normal nature of item distribution, both support the validity of MD as a psychological disorder, which should be considered as a potential addition to future psychiatric diagnostic manuals.